Crisis risk measurements – trade with credit default swaps against measurements of the capital trade dynamics - Paskaleva, Mariya Georgieva (International Journal of Contemporary Economics and Administrative Sciences, 2017)
This study represents the increasing significance of credit default swaps for European capital markets, namely Germany, France, Belgium, Ireland, Italy, Portugal, Spain, Greece, Bulgaria and Romania. The period of analysis is between 2003- 2016 years. After developing a theoretical and empirical framework to model the relationship between credit default swap market and capital market, we apply an empirical research which uses logistic regression. Our dataset assesses the ability of CDS to predict financial crisis at stock markets. Regarding sovereign credit default swaps as reflection of credit risk, we find them to be a significant indicator explaining the periods proceeding financial crises, especially to developed capital markets.